2021
DOI: 10.3390/jpm11020158
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interactome Proposes Subtype-Specific Biomarkers and Potential Therapeutics in Renal Cell Carcinomas

Abstract: Although many studies have been conducted on single gene therapies in cancer patients, the reality is that tumor arises from different coordinating protein groups. Unveiling perturbations in protein interactome related to the tumor formation may contribute to the development of effective diagnosis, treatment strategies, and prognosis. In this study, considering the clinical and transcriptome data of three Renal Cell Carcinoma (RCC) subtypes (ccRCC, pRCC, and chRCC) retrieved from The Cancer Genome Atlas (TCGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We carried out SBVS using the docking method on FDA-Approved drugs of the ZINC15 database to recognize new SENP1 inhibitors. Molecular docking is the best method to quickly estimate the binding conformations of ligands that are energy-efficient to interact with a pharmacological receptor site and has obtained popularity as a tool to store time and costs in the pipeline of drug discovery and development ( Kaushik et al, 2020 ; Caliskan et al, 2021 ). ZINC15 joins biological activities of drugs, gene products, and natural products with commercial availability ( Irwin and Shoichet, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…We carried out SBVS using the docking method on FDA-Approved drugs of the ZINC15 database to recognize new SENP1 inhibitors. Molecular docking is the best method to quickly estimate the binding conformations of ligands that are energy-efficient to interact with a pharmacological receptor site and has obtained popularity as a tool to store time and costs in the pipeline of drug discovery and development ( Kaushik et al, 2020 ; Caliskan et al, 2021 ). ZINC15 joins biological activities of drugs, gene products, and natural products with commercial availability ( Irwin and Shoichet, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…We applied our constructed differential interactome algorithm, which had proven to be a powerful tool in other studies [8,31,32], for the protein-protein interactome data on hallmarks of cancer. Our results revealed DIHCPs showing remarkable changes in the interaction patterns of patients during the transition from the "normal" phenotype to the "cancer" phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Many successful or unsuccessful algorithms are developed today for this purpose. The "differential interactome algorithm" used in this study has been shown to be successful in various cancers [18,[49][50][51], but in the present study, it was applied for the rst time to HNSC cancer considering HPV status. We discovered DIPs that exhibit remarkable changes in their interaction patterns during the transition from the "HPV16-positive HNSC cancer" phenotype to the "HPV-negative HNSC cancer" phenotype.…”
Section: Discussionmentioning
confidence: 99%